KAJIAN POLA PENGEMBANGAN UMKM DI KAMPUNG BATIK LAWEYAN MELALUI MODAL SOSIAL DALAM MENGHADAPI PERDAGANGAN BEBAS KAWASAN ASEAN - Setyanto, Alief Rakhman; Samudro, Bhimo Rizky; Pratama, Yogi Pasca (EP FEB UNS, 2015)
In the development of the national economy in Indonesia, which were prioritized Micro, Small and Medium Enterprises (SMEs). SMEs become the backbone of a democratic economic system to reduce the problems of poverty and development were able to expand the economic base and can make a significant contribution to improving the local economy and the resilience of the national economyLaweyan Batik SMEs in order to survive in the current free trade is needed pattern appropriate strategy to maintain the existence of Batik Laweyan SMEs in trade flows freely.In a study using qualitative methods of data collection method interviews, participant observation and documentation. Then the data analysis techniques in this study using data collection, data reduction, data display and conclusionResults from the study suggests that the pattern of development of SMEs Batik Laweyan by innovating, updating product and then applying social capital to expand business network networkThe conclusion of the study outlined that social capital relationship with Innovation and cooperation in creating SME development is closely it is evident that most employers have defined it in their business. Always innovating in production and implement social capital in developing the business and working with business partners so that businesses can thrive batik production Keywords: SMEs, Batik Laweyan, Innovation and Social CapitalJEL Classification: F61, M29, D02